PERAN UNDANG-UNDANG NO 5 TAHUN 1990 DALAM MENCEGAH PERDAGANGAN SATWA LIAR YANG DILINDUNGI (STUDI PUTUSAN NOMOR 436/PID.SUS/2023/PN JKT.UTR): The Role of Law No. 5 Of 1990 Preventing Sale Protected Wildlife (Study Verdict Number 436/Pid.Sus/2023/Pn Jkt.Utr) - Dava Tubagus Rahmat; Ermania Widjajanti (Reformasi Hukum Trisakti, 2025)
The iIIegal trade in protected wiIdIife poses a serious threat to biodiversity conservation in Indonesia. For the case study used is the North Jakarta District Court Number 436/Pid.Sus/2023/PN Jkt.Utr. The question how the roIe of Law Number 5 of 1990 concerning the Conservation of NaturaI Resources and Ecosystems prevents the trade on protected wiIdIife?. This research uses normative IegaI method with descriptive-anaIyticaI approach based on secondary data. The resuIts show that the KSDAE Law provides a strong IegaI roIe in prohibiting the iIIegaI trade of wiIdIife, with criminaI penaIties stipuIating severe sanctions to provide a deterrent effect. In addition, this Iaw pIays a roIe in encouraging pubIic awareness through conservation education, but the roIe of the KSDAE Law faces chaIIenges in the form of weak Iaw enforcement, Iack of supervision, and its oId age. ConcuIsion, there shouId be IegaI reforms and more pubIic participation to support wiIdIife conservation and sustainabiIity in Indonesia.